1999
DOI: 10.1128/.67.4.2040-2044.1999
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of Pseudomonas aeruginosa Type III-Secreted Proteins on CHO Cells

Abstract: A strain of Pseudomonas aeruginosa that fails to express known type III-secreted effector proteins was constructed as an expression host. Individual effectors were expressed in trans, and their biological effects on CHO cells were assessed in an acute cellular infection model. Intoxication with ExoS, ExoT, or ExoY resulted in alterations in cell morphology. As shown in previous genetic studies, ExoU expression was linked to acute cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 18 publications
(32 reference statements)
2
50
1
Order By: Relevance
“…ExoY-mediated cell rounding associated with adenylate cyclase activity has been shown previously [20]. The present study shows that, as might be expected, this in-volves significant changes in actin distribution and cytoskeleton integrity.…”
Section: Discussionsupporting
confidence: 89%
“…ExoY-mediated cell rounding associated with adenylate cyclase activity has been shown previously [20]. The present study shows that, as might be expected, this in-volves significant changes in actin distribution and cytoskeleton integrity.…”
Section: Discussionsupporting
confidence: 89%
“…Our results indicated that exotoxin A effect did not increase when iron was absent and that exotoxin A was not involved in killing A. castellanii. Previous studies have shown that although the PA103 strain produced large amounts of exotoxin A in vitro (Vallis et al 1999), it was not involved in killing epithelial cells (Apodaca et al 1995). Iron is required to enhance virulence of many bacteria, such as P. aeruginosa, by affecting host cell lysis (Sirtharan 2006), which might explain why the co-cultivated amoeba population died within 5 days in the presence of iron whereas the population died within 8 days when iron was depleted.…”
Section: -200 Bpmentioning
confidence: 99%
“…To date, TTSS effector proteins included four proteins, ExoS, ExoT, ExoU, and ExoY (Sato and Frank 2004). Vallis et al (1999) observed that ExoU and ExoS are cytotoxic causing irreversible damage in morphology and cell membranes of eukaryotes as well as necrotic death, while ExoT and ExoY have no cytotoxic effects. Shaver and Hauser (2004) assessed effects of TTSS proteins on a mouse model of acute pneumonia by measurements of mortality, as well as bacterial persistence in the lung, and they found that secretion of ExoU had the greatest impact on virulence while secretion of ExoS had an intermediate effect and ExoT had a minor effect.…”
Section: -200 Bpmentioning
confidence: 99%
“…ExoS ultimately causes cell death whereas ExoT does not. ExoY alters cell morphology but does not produce cell death (Yahr et al ., 1998;Vallis et al ., 1999).…”
Section: Introductionmentioning
confidence: 99%